Oridonin Delays Aging Through the AKT Signaling Pathway - An, Yongpan; Zhu, Jie; Wang, Xin; Sun, Xinpei; Luo, Chunxiong; Zhang, Yukun; Ye, Yuwei; Li, Xiaowei; Abulizi, Abudumijiti; Huang, Zhizhen; Zhang, Hang; Yang, Baoxue; et al. (Frontiers in Pharmacology, 2022)
Aging is a major risk factor for chronic diseases and disability in humans. Nowadays, no effective anti-aging treatment is available clinically. In this study, oridonin was selected based on the drug screening strategy similar to Connectivity MAP (CMAP) but upon transcriptomes of 102 traditional Chinese medicines (TCM) treated cell lines. Oridonin is a diterpenoid isolated from Rabdosia rubescens. As reported, Oridonin exhibits a variety of pharmacological activities, including antitumor, antibacterial and anti-inflammatory activities. Here, we found that oridonin inhibited cellular senescence in human diploid fibroblasts (2BS and WI-38), manifested by decreased senescence-associated β-galactosidase (SA-β-gal) staining. Compared with the elderly control group, the positive cell rate in the oridonin intervention group was reduced to 48.5%. Notably, oridonin prolonged the lifespan of yeast by 48.9%, and extended the average life span of naturally aged mice by 21.6%. Our mice behavior experiments exhibited that oridonin significantly improved the health status of naturally aged mice. In addition, oridonin also delayed doxorubicin-induced cellular senescence and mouse senescence. Compared with the model group, the percentage of SA-β-gal positive cells in the oridonin treatment group was reduced to 59.8%. It extended the average lifespan of mice by 53.8% and improved healthspan. Mechanistically, we showed that oridonin delayed aging through the AKT signaling pathway and reversed the genetic changes caused by doxorubicin-induced cell senescence. Therefore, oridonin is a potential candidate for the development of anti-aging drugs.